Pengembangan dan Pertambahan Nilai Pada Produk Purun Inovatif Berpeluang Lolos Kurasi Ekspor - Hesty Heryani; Tuti Heiriyani; Dessy Maulidya Maharani; Arif Pangestu (Universitas Lambung Mangkurat, 2023)
Kampung Purun, Palam, Banjarbaru is well-known as the development of creative industries making purun woven products. The products are in the form of various bags, hats, mats and tissue boxes as well as many other various products. The resulting product has a variety of colors, but in the coloring process the craftsmen still use chemical dyes which are not environmentally friendly. Besides that, the product design is still not varied. This service aimed at innovating purun products produced by the villagers of Kampung Purun, especially the Galoeh Bandjar group by redesigning and innovating the dyes used, namely using natural dyes to boost the chances of purun products being able to pass the export curation. Natural dyes were produced from a combination of jengkol skin and sappan wood, with various formulations developed based on previous research results. The best formula used was 12 : 1 : 7 consisting of water : cup : jengkol skin. The jengkol skin used was waste from the Jaring culinary production process. Dyes were made by boiling the two ingredients. Furthermore, the production stages by designing, coloring, determining color composition and evaluating product quality were carried out at the Banjarbaru Government Packaging House. The resulting color was brownish red and ready to be applied to purun products. The results of the curation by the Packaging House stated that the innovative purun product was feasible to be marketed from a quality standpoint. The selling price of the product was set at Rp. 46,000, - with a production cost of Rp. 36,621, - per unit. This means that there is an additional value of IDR 10,379.